2019
DOI: 10.1002/aic.16570
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic mechanism of selective cocrystallization explored by MD simulation and phase diagram analysis

Abstract: The thermodynamic mechanism of selective cocrystallization was investigated by combination of molecular dynamics (MD) simulations and phase diagram analysis, using system of urea and cresol isomers as model compounds. Hansen solubility parameters (HSPs) models were utilized to predict miscibility and cocrystal formation. Thermodynamic phase diagrams of cresol isomers and urea were measured with the help of process analysis technology. MD simulations were performed to investigate the intermolecular interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…This is due to the inherent deficiency of the group contribution methods which assume that the physical properties of a compound are to some extent determined by the sum of the contributions of structural groups and functional groups in the repeating units of the molecule or polymer, while ignoring the fact that a given group's contribution in one environment is not necessarily the same as its contribution in another. 39 Based on the above analysis, it can be concluded that there are some relationships between the Glu-Me solubility and the solubility parameters, but the solubility behavior of Glu-Me cannot be completely explained through HSPs. There are several factors which may also affect the miscibility of Glu-Me in the selected solvents, such as the solvent polarity, molecular structure of the solute and solvent, hydrogen bonds, and so on.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…This is due to the inherent deficiency of the group contribution methods which assume that the physical properties of a compound are to some extent determined by the sum of the contributions of structural groups and functional groups in the repeating units of the molecule or polymer, while ignoring the fact that a given group's contribution in one environment is not necessarily the same as its contribution in another. 39 Based on the above analysis, it can be concluded that there are some relationships between the Glu-Me solubility and the solubility parameters, but the solubility behavior of Glu-Me cannot be completely explained through HSPs. There are several factors which may also affect the miscibility of Glu-Me in the selected solvents, such as the solvent polarity, molecular structure of the solute and solvent, hydrogen bonds, and so on.…”
Section: Resultsmentioning
confidence: 93%
“…This indicates that the solubility parameter of Δδ t cannot be used to compare the solubility of Glu-Me in the selected solvents except for methanol (Δδ t = 6.70 MPa 0.5 < 7 MPa 0.5 ). This is due to the inherent deficiency of the group contribution methods which assume that the physical properties of a compound are to some extent determined by the sum of the contributions of structural groups and functional groups in the repeating units of the molecule or polymer, while ignoring the fact that a given group’s contribution in one environment is not necessarily the same as its contribution in another …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Recently, perturbed-chain statistical associating fluid theory (PC-SAFT) has also been successfully applied to describe the solid−liquid equilibrium of drug-related systems and calculate the thermodynamic properties of the systems accurately. 11−15 Furthermore, the Hansen solubility parameter, 7,16 molecular dynamics simulations, 17,18 COSMO-SAC, 19 and other methods are also proposed to achieve solubility prediction. Although many theoretical advances have been made, it is still difficult to achieve an accurate and…”
Section: Introductionmentioning
confidence: 99%
“…Solid–liquid equilibrium theory is another effective method to calculate the solubility as shown in eq , where the activity coefficient can be estimated by the activity coefficient model, such as the Wilson equation, UNIFAC equation, and UNIQUAC equation . Recently, perturbed-chain statistical associating fluid theory (PC-SAFT) has also been successfully applied to describe the solid–liquid equilibrium of drug-related systems and calculate the thermodynamic properties of the systems accurately. Furthermore, the Hansen solubility parameter, , molecular dynamics simulations, , COSMO-SAC, and other methods are also proposed to achieve solubility prediction. Although many theoretical advances have been made, it is still difficult to achieve an accurate and quantitative prediction of drug solubility as a function of temperature in the full absence of experimental data …”
Section: Introductionmentioning
confidence: 99%